Rapid and Body Weight–Independent Improvement of Endothelial and High-Density Lipoprotein Function After Roux-en-Y Gastric Bypass. Issue 10 (10th March 2015) - Osto, Elena; Doytcheva, Petia; Corteville, Caroline; Bueter, Marco; Dörig, Claudia; Stivala, Simona; Buhmann, Helena; Colin, Sophie; Rohrer, Lucia; Hasballa, Reda; Tailleux, Anne; Wolfrum, Christian; et al.
<x xml:space="preserve">Abstract</x> Background— Roux-en-Y gastric bypass (RYGB) reduces body weight and cardiovascular mortality in morbidly obese patients. Glucagon-like peptide-1 (GLP-1) seems to mediate the metabolic benefits of RYGB partly in a weight loss–independent manner. The present study investigated in rats and patients whether obesity-induced endothelial and high-density lipoprotein (HDL) dysfunction is rapidly improved after RYGB via a GLP-1–dependent mechanism. Methods and Results— Eight days after RYGB in diet-induced obese rats, higher plasma levels of bile acids and GLP-1 were associated with improved endothelium-dependent relaxation compared with sham-operated controls fed ad libitum and sham-operated rats that were weight matched to those undergoing RYGB. Compared with the sham-operated rats, RYGB improved nitric oxide (NO) bioavailability resulting from higher endothelial Akt/NO synthase activation, reduced c-Jun amino terminal kinase phosphorylation, and decreased oxidative stress. The protective effects of RYGB were prevented by the GLP-1 receptor antagonist exendin9-39 (10 μg·kg−1·h−1). Furthermore, in patients and rats, RYGB rapidly reversed HDL dysfunction and restored the endothelium-protective properties of the lipoprotein, including endothelial NO synthase activation, NO production, and anti-inflammatory, antiapoptotic, and antioxidant effects. Finally, RYGB restored HDL-mediated cholesterol efflux capacity. To demonstrate the role of increased GLP-1 signaling, sham-operated control rats were treated for 8 days with the GLP-1 analog liraglutide (0.2 mg/kg twice daily), which restored NO bioavailability and improved endothelium-dependent relaxations and HDL endothelium-protective properties, mimicking the effects of RYGB. Conclusions— RYGB rapidly reverses obesity-induced endothelial dysfunction and restores the endothelium-protective properties of HDL via a GLP-1–mediated mechanism. The present translational findings in rats and patients unmask novel, weight-independent mechanisms of cardiovascular protection in morbid obesity.